Jam‘u at-Taksīr dan Tejemahnya dalam “Al-Quranul Karim Bacaan Mulia” karya H.B Jassin (Kajian Shorfiyah) - Tia Nuraeni; Aang Saeful Milah; Hatta Raharja; Lalu Turjiman Ahmad; Endang Saeful Anwar (Jurusan Bahasa dan Sastra Arab Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2019)
This reaserch is discuss about forms of the Broken Plural along with the translation contained in “Al-Qur’anul Karim Bacaan Mulia”, written by Indosesian writer he is H.B Jassin who has translated Al-Qur’an by poetic language. The restricting the problem of this reaserch are the only forms of the Broken Plural in Letter of Al-Noor. In this study, the researcher used the qualitive method of library study. Qualitive method are research methods that produce descriptive data in the form of written words, from books relating to research problems. Using the theory of morphologi to determinate the patterns of the Broken Plural in the object of studies. As for the results, found 31 of Broken Plurals by denying some of the same words. There are 14 words of Lesser Broken Plural in Letter of Al-Noor with three patterns, which are اَفعُل، افعِلة ، افعال. There are 14 words of Greater Broken Plural with six patterns, which are فعلاء، فعول، فعال، فِعْلان، فَعلى، وفعُل, and 3 words of Ultimate Plural (Ṣīgah Muntaha al-Jumu‘) which are: ف واعل، فعاليل، مفاعل.Then the suitability of H.B Jassin in translating the Broken Plural in his creation, it’s “Al-Qur’anul Karim Bacaan Mulia”.